Pengabdian kepada Masyarakat: Penyuluhan Pengetahuan Manajemen Stres Bagi Pelaku UMKM di Azalea Depok - Emilisa, Netania; Indriyarti, Eko Retno; Yusran, Husna Leila; Wahyuni, Lidia; Dizar, Shafrani (Universitas Bunda Mulia, 2023)
MSME actors and employees at work often feel stressed either because of the work environment or the impact of problems brought from outside the work environment. Even more so when it is associated with the prolonged impact of the COVID-19 pandemic. This can further make employees anxious to continue working. Business conditions in this case also become a determining factor. In addition, internal and external problems experienced by employees can also be an additional factor in forming anxiety to continue working which in the long run can create stress at a certain level. These things were used as the background for the initial situation analysis as a detector of partner problems, namely employees working at Azalea's Micro, Small and Medium Enterprises (MSMEs) in Depok. The implementing team then determined the method of Community Service activities to be carried out, namely counseling. This PkM activity was held on March 8-9, 2023, face to face on the spot. During the material bidding process, activities went well and smoothly. Based on the results of the feedback obtained from the 32 participants who took part, the participants felt that this PkM activity provided additional knowledge for the participants, especially regarding stress management. In addition, the participants also felt that the topics raised and presented to the participants matched the participants' needs in recognizing stress to managing stress in the workplace. The participants also felt that the activities provided were sufficient in terms of implementation time. Furthermore, the participants hoped that other activities could be carried out in the future.